Sorption-Desorption Behavior of Imazethapyr and Imazapic on Six Brazilian Soils - MARINHO,M.I.C. (2018)
ABSTRACT: The characterization of sorption-desorption for imazethapyr and imazapic in six agricultural soils was performed to assess the availability of these herbicides in pollution processes. In this pursuit, the batch equilibrium method and high-performance liquid chromatography were used. The magnitude of Kf values ranging from 0.38 to 2.52 mg1-n kg-1 Ln for imazethapyr and 0.43 to 2.72 mg1-n kg-1 Ln for imazapic indicate weak sorption in the evaluated soils. Soil pH (5.1 to 6.1) and iron oxalate affect sorption-desorption of both herbicides but the type and percentage of clay can be the main factor affecting these two processes. A high desorption percentage (>70%) was found in Regosol, Dystric Plinthosol, Ferralsol (for both herbicides), and Dystric Gleysol (only imazapic) soils, which implies in leaching risks of these imidazolinone herbicides into groundwater. Lower desorption (<50%) was found in Cambisol and Alisol (for both herbicides), and (~50%) in Dystric Gleysol (only imazethapyr) soils, indicating that these herbicides could potentially injure the sensitive crops grown in rotation.